Wall protection slurry for underground scour prevention wall, preparation method and application

By using bentonite, carboxymethylcellulose, soda ash, sodium silicate, nanoalumina and modified polytetrafluoroethylene fibers in wall guard mud, the traditional mud was solved when constructing in medium-coarse sand and egg gravel formations. The stability and reuse issues have achieved efficient wall protection and anti-collapse effects, and achieved green and environmentally friendly construction and mud recycling.

CN119161164APending Publication Date: 2024-12-20BEIJING JING SHUI CONSTR GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411393661.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Traditional wall-protecting mud is prone to quality problems such as collapse, shrinkage, mud and sand clamping when constructed in medium-coarse sand and egg gravel formations, and the stability of the specific gravity, pH value, viscosity and other indicators is poor, so the stability of the groove wall cannot be guaranteed. , and the waste liquid rate is high, making it impossible to achieve green and environmentally friendly recycling.

Method used

Using a wall protection mud including bentonite, carboxymethylcellulose, soda ash, sodium silicate, nano-alumina and modified polytetrafluoroethylene fibers, the preparation method and regeneration treatment technology of modified polytetrafluoroethylene fibers are improved. The viscosity, density and stability of mud enhances its filling and support capabilities in low-density formations and realizes circulating regeneration of mud.

Benefits of technology

When constructing in the medium-coarse sand and egg gravel formation, the stability of the trough wall and anti-collapse effect are significantly improved, the cost is reduced, and the construction is achieved is green and environmentally friendly. The regeneration and treatment of the mud is simple and easy to use, and it is suitable for Various construction situations.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of building construction materials, and discloses wall protection slurry for an underground scour-proof wall, a preparation method and application. Raw materials of the wall protecting slurry for the underground impingement wall comprise bentonite, carboxymethyl cellulose, sodium carbonate, sodium silicate, nanometer aluminum oxide and modified polytetrafluoroethylene fibers, and the modified polytetrafluoroethylene fibers are prepared through reaction of polytetrafluoroethylene fibers, MPTMS and butyl acrylate. All indexes of the wall protection slurry for the underground scour prevention wall can meet the requirements of circulating slurry indexes, the wall protection slurry can be well suitable for construction of the underground scour prevention wall of a stratum with much sand and gravel distribution, low compactness and high porosity, the slurry wall protection and collapse prevention effects are good, and the stability of a groove wall is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building construction materials, and in particular to a wall protection slurry for underground anti-collision walls, a preparation method and an application thereof. Background Art

[0002] Underground anti-collision walls have the advantages of mature technology, high rigidity, good integrity, and good water-stopping effect. In recent years, they have become a widely used retaining structure in foundation pit construction. In the early stage of underground continuous wall construction, segmented trenching is often used, and then steel cages are inserted into the trench sections and concrete is poured. In the segmented trenching process, mud wall protection is often used.

[0003] During the trenching process of the underground anti-scouring wall, the wall protection mud will be deposited on the surface of the trench wall to form a mud skin, which protects the trench wall. At the same time, the water and soil pressure of the mud and soil layer in the trench is balanced, and the trench wall remains stable and does not collapse.

[0004] When the strata in the construction area are mainly composed of medium-coarse sand and gravel, the density is low, the porosity is high and the water level is low. When using traditional formula wall protection mud for trenching, it is easy to collapse and cause bulging of the underground anti-collision wall. At this time, the wall protection mud is required to have a higher specific gravity and viscosity stability.

[0005] Most traditional muds use CMC (sodium carboxymethyl cellulose) as a thickener. The indicators of this type of traditional mud cannot meet the wall protection requirements of "formations with poor self-supporting properties such as fine sand and fine sand". It is easy to have shrinkage holes in the trench wall or local collapse of the trench wall. Mud and sand are easily included in the wall joints, leading to leakage and other quality problems. At the same time, the stability of mud indicators such as specific gravity, pH value, and viscosity are also easily affected by groundwater, and the waste liquid rate is high, and the stability of the trench wall cannot be guaranteed.

[0006] Therefore, developing a slurry that can ensure the quality of trenching, has good wall protection performance, high slurry recycling rate and is green and environmentally friendly has important practical significance for the advancement of underground wall construction. Summary of the invention

[0007] In order to solve the above technical problems, a low-cost, pollution-free, anti-collapse and strong wall-fixing ability underground impact wall retaining mud is developed, which can be suitable for the construction of underground impact wall projects in strata dominated by medium-coarse sand and gravel, with low density and high porosity. The present application provides a kind of underground impact wall retaining mud, preparation method and application.

[0008] In a first aspect, the present application provides 1. a wall protection slurry for underground anti-collision wall, comprising the following raw materials in parts by weight: 75-100 parts of bentonite, 0.7-1.2 parts of carboxymethyl cellulose, 1.6-2.5 parts of soda ash, 1000 parts of water, 12-25 parts of sodium silicate, 5-10 parts of nano-alumina, 8-16 parts of modified polytetrafluoroethylene fiber; The modified polytetrafluoroethylene fiber is prepared by reacting polytetrafluoroethylene fiber with MPTMS and butyl acrylate.

[0009] By adopting the above technical solution, bentonite is a hydrated clay mineral mainly composed of montmorillonite, which has the properties of swelling, adhesion and adsorption. In addition, bentonite has a strong slurry-making ability, and the sand content of the manufactured mud is extremely low. The density of the original bentonite slurry is small, so it can carry more debris, thereby greatly increasing the density of the mud in a short time after the mud enters the groove, increasing the relative density of the mud, and increasing its ability to maintain the stability of the groove wall. Modified polytetrafluoroethylene fiber is used to control the suspended matter in the mud, and can play a net-like role in the mud, greatly increasing the suspended debris of the mud, and increasing the viscosity and density of the mud.

[0010] Carboxymethyl cellulose helps to improve the viscosity, suspension and other characteristics of the mud and improve the overall performance of the mud. Adding dispersant soda ash to the mud is conducive to the formation of a good mud skin, and it will also reduce the viscosity of the mud, so the amount of soda ash added needs to be reasonably controlled. Sodium silicate and alumina are compounded, and alumina powder is dispersed in sodium silicate solution to form aluminum silicate gel, which has a high specific surface area and strong adsorption performance. The adsorbed metal cations are concentrated around the colloid, making the solid distribution inside the mud more uniform.

[0011] Furthermore, the preparation method of the modified polytetrafluoroethylene fiber comprises the following steps: adding polytetrafluoroethylene fiber, MPTMS and butyl acrylate into an organic solvent, ultrasonicating, adding an initiator, heating to 70-90°C, keeping the temperature constant and reacting for 1.5-3h; reacting again under ethanol reflux for 10-15h, filtering and collecting the residue, and drying to obtain the modified polytetrafluoroethylene fiber.

[0012] Preferably, the weight ratio of the polytetrafluoroethylene fiber, MPTMS, butyl acrylate and initiator is 10-15:1-2:1-2.5:0.8.

[0013] By adopting the above technical scheme, the modified polytetrafluoroethylene fiber is grafted with polybutyl acrylate molecular chains on the hydrophobic polytetrafluoroethylene fiber surface, which weakens the hydrophobicity of the modified polytetrafluoroethylene fiber. Because the polytetrafluoroethylene fiber itself has a high density, under the combined effect of its own gravity and other forces, most of the modified polytetrafluoroethylene fibers can be suspended in the mud, can better bond the colloid in the mud, improve the relative density of the mud, and increase its ability to maintain the stability of the groove wall. It can quickly fill and support the formation with low density and high porosity, which is mainly composed of medium-coarse sand and gravel, maintain the stability of the groove wall and prevent collapse.

[0014] Furthermore, the length of the modified polytetrafluoroethylene fiber is 5-25 mm.

[0015] Furthermore, the bentonite is sodium-based bentonite with a particle size of 150-300 meshes.

[0016] Furthermore, the content of montmorillonite in the bentonite is 60-80wt%.

[0017] By adopting the above technical scheme, the physical and chemical properties and process technology performance of sodium-based bentonite are superior to those of calcium-based bentonite, which are mainly manifested in: slow water absorption speed, but large water absorption rate and expansion multiple, high cation exchange capacity, good dispersibility in water medium, and high colloid value; its colloidal suspension has good thixotropy, viscosity, lubricity and thermal stability; it has high plasticity and strong adhesion; high hot wet tensile strength and dry compressive strength; the higher the content of montmorillonite in the bentonite, the stronger the water absorption and expansion capacity of the bentonite, thereby forming a gel-like substance.

[0018] In a second aspect, the present application provides a method for preparing the above-mentioned underground anti-collision wall slurry, comprising the following steps: S1, dissolving carboxymethyl cellulose in water to prepare a 10wt% carboxymethyl cellulose solution, letting it stand for 4-8h to obtain a carboxymethyl cellulose solution for later use; S2. Add bentonite, sodium silicate, nano-alumina and the remainder of water into a mixing drum, stir for 3-10 minutes, add soda ash, stir for 3-10 minutes, add modified polytetrafluoroethylene fiber, stir for 10-20 minutes, and let stand until the bentonite particles are completely hydrated and expanded to obtain the wall protection mud for underground anti-collision walls.

[0019] On the third aspect, the present application provides the application of the above-mentioned underground impact wall retaining slurry in the field of underground impact wall construction.

[0020] Furthermore, the wall slurry for underground anti-collision wall uses the waste slurry after one cycle in the construction process, regenerates it, and reuses it. The regeneration method includes the following steps: T1. Pump the waste mud into a waste mud pool and let it stand for 20-30 hours to precipitate large-sized solid soil particles and fibers in the waste mud; then use the filter screen of the waste mud pool to separate the solid soil particles, fibers and mud, and collect the separated mud to obtain primary mud; T2. Add a first flocculant to the primary mud obtained in step T1, the first flocculant reacts with impurities in the primary mud to form floccules, and let it stand for 5-10 hours; add a second flocculant, the second flocculant promotes the floccules to form precipitation, and let it stand for 10-15 hours to precipitate soil particles with a particle size of less than 0.1 mm to obtain a premixed liquid; mix the premixed liquid with the raw materials used for preparing the wall protection mud for underground anti-collision walls to obtain mud, thereby completing the regeneration of the waste mud.

[0021] Furthermore, in step T2, the first flocculant is selected from one of ferric chloride, aluminum chloride, and alum, and the dosage of the first flocculant is 7-12 g / L; the second flocculant is selected from one of polyacrylamide, sodium polyacrylate, and starch, and the dosage of the second flocculant is 3-5 g / L.

[0022] Furthermore, 10. in the step T2, the mud prepared using the premixed liquid comprises the following raw materials in parts by weight: 25-40 parts of bentonite, 0.4-0.8 parts of carboxymethyl cellulose, 0.5-1 parts of soda ash, 800 parts of premixed liquid, 200 parts of water, 5-9 parts of sodium silicate, 3-7 parts of nano-alumina, and 8-16 parts of modified polytetrafluoroethylene fiber.

[0023] By adopting the above technical solution, the above treatment method combines physical sedimentation with chemical separation, removes fine soil particles in the waste mud, and realizes the reuse of the waste mud.

[0024] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The various indicators of the underground anti-collision wall slurry prepared in the present application can meet the requirements of circulating mud indicators, and can be well applied to the construction of underground anti-collision walls in strata with a large distribution of sand and gravel, low density and high porosity. The slurry has good wall protection and anti-collapse effects, and good trench wall stability.

[0025] 2. The underground anti-collision wall retaining slurry prepared in this application has low cost and is green and environmentally friendly; and the mud regeneration treatment method is simple and easy, and is suitable for construction in various situations. DETAILED DESCRIPTION

[0026] The present application designs a wall protection slurry for underground anti-collision walls, comprising the following raw materials in parts by weight: 75-100 parts of bentonite, 0.7-1.2 parts of carboxymethyl cellulose, 1.6-2.5 parts of soda ash, 1000 parts of water, 12-25 parts of sodium silicate, 5-10 parts of nano-alumina, 8-16 parts of modified polytetrafluoroethylene fiber; The modified polytetrafluoroethylene fiber is prepared by reacting polytetrafluoroethylene fiber with MPTMS and butyl acrylate.

[0027] The underground anti-collision wall slurry of the present application is prepared by the following method, comprising the following steps: S1, dissolving carboxymethyl cellulose in water to prepare a 10wt% carboxymethyl cellulose solution, letting it stand for 4-8h to obtain a carboxymethyl cellulose solution for later use; S2. Add bentonite, sodium silicate, nano-alumina and the remainder of water into a mixing drum, stir for 3-10 minutes, add soda ash, stir for 3-10 minutes, add modified polytetrafluoroethylene fiber, stir for 10-20 minutes, and let stand until the bentonite particles are completely hydrated and expanded to obtain the wall protection mud for underground anti-collision walls.

[0028] The underground anti-collision wall retaining mud of the present application can be used in the field of underground anti-collision wall construction. The underground anti-collision wall retaining mud of the present application uses the waste mud after a cycle in the construction process, regenerates it, and reuses it, including the following steps: T1, pumping the waste mud into the waste slurry pool, standing for 20-30 hours, and precipitating the large-size solid soil particles and fibers in the waste mud; then using the filter screen of the waste slurry pool to separate the solid soil particles, fibers and mud, and collecting the separated mud to obtain primary mud; T2, adding the first flocculant to the primary mud obtained in step T1, the first flocculant reacts with the impurities in the primary mud to form floccules, and standing for 5-10 hours; adding the second flocculant, the second flocculant promotes the formation of floccules and precipitation, standing for 10-15 hours, so that the soil particles with a particle size of less than 0.1mm are precipitated to obtain a premixed liquid; the premixed liquid is mixed with the raw materials used to prepare the underground anti-collision wall retaining mud to obtain mud, and the regeneration of the waste mud is completed.

[0029] The present application is further described in detail below in conjunction with specific embodiments.

[0030] Example 1 The wall protection slurry for underground anti-collision wall in Example 1 includes the following raw materials in parts by weight: 75 parts of bentonite, 0.8 parts of carboxymethyl cellulose, 2 parts of soda ash, 1000 parts of water, 15 parts of sodium silicate, 7 parts of nano-alumina, and 11 parts of modified polytetrafluoroethylene fiber.

[0031] The average length of the modified polytetrafluoroethylene fibers in Example 1 was about 16 mm.

[0032] The bentonite in Example 1 is sodium-based bentonite with a particle size of 200 mesh and an average montmorillonite content of about 77 wt %.

[0033] The preparation method of modified polytetrafluoroethylene fiber in Example 1 comprises the following steps: adding polytetrafluoroethylene fiber, MPTMS and butyl acrylate to a 50% volume fraction ethanol solution, ultrasonicating for 10 minutes, adding diisopropylbenzene peroxide, heating to 90°C, keeping the temperature constant for 2.5 hours; reacting again for 12 hours under ethanol reflux, filtering and taking the residue, drying, and obtaining modified polytetrafluoroethylene fiber. Among them, the weight ratio of polytetrafluoroethylene fiber, MPTMS, butyl acrylate and diisopropylbenzene peroxide is 11:1.2:2:0.8. That is, the amount of MPTMS is 1.2 parts by weight, the amount of butyl acrylate is 2 parts by weight, and the amount of diisopropylbenzene peroxide is 0.8 parts by weight.

[0034] The method for preparing the underground anti-collision wall slurry in Example 1 comprises the following steps: S1, dissolving 0.8 parts by weight of carboxymethyl cellulose in 1 part by weight of water to prepare a 10wt% carboxymethyl cellulose solution, and letting it stand for 6 hours to obtain a carboxymethyl cellulose solution for later use; S2. Add 75 parts by weight of bentonite, 15 parts by weight of sodium silicate, 7 parts by weight of nano alumina and the balance of water into a mixing drum, stir for 5 minutes, add soda ash, stir for 10 minutes, add 11 parts by weight of modified polytetrafluoroethylene fiber, stir for 20 minutes, and let stand for about 4 hours until the bentonite particles are completely hydrated and expanded to obtain a retaining mud for an underground anti-collision wall.

[0035] The relative density of the mud for underground impact wall protection in Example 1 was measured to be 1.12, the viscosity was 19s, the sand content was 6%, the colloid rate was 97%, the water loss rate was 24ml / min, the mud skin thickness was 1mm / 30min, the static shear force was 1.09Pa, and the pH value was 8.5, which met the requirements for mud for strata with low density and high porosity in the technical regulations for underground impact wall inspection, which were mainly medium-coarse sand and gravel.

[0036] Example 2 Example 2 is based on Example 1, with the difference being that the amount of raw materials used in the underground impact wall slurry in Example 2 is different.

[0037] The wall protection slurry for underground anti-collision wall in Example 2 includes the following raw materials in parts by weight: 90 parts of bentonite, 0.8 parts of carboxymethyl cellulose, 2 parts of soda ash, 1000 parts of water, 15 parts of sodium silicate, 7 parts of nano-alumina, and 11 parts of modified polytetrafluoroethylene fiber.

[0038] The relative density of the mud for underground impact wall protection in Example 2 was measured to be 1.14, the viscosity was 23s, the sand content was 5%, the colloid rate was 98%, the water loss rate was 12ml / min, the mud skin thickness was 1mm / 30min, the static shear force was 4.2Pa, and the pH value was 9, which met the requirements for mud for strata with a geological condition dominated by medium-coarse sand and gravel, low density and high porosity in the technical regulations for underground impact wall inspection.

[0039] Example 3 Example 3 is based on Example 1, with the difference being that the amount of raw materials used in the underground anti-collision wall slurry in Example 3 is different.

[0040] The wall protection slurry for underground anti-collision wall in Example 3 includes the following raw materials in parts by weight: 110 parts of bentonite, 0.8 parts of carboxymethyl cellulose, 2 parts of soda ash, 1000 parts of water, 15 parts of sodium silicate, 7 parts of nano-alumina, and 11 parts of modified polytetrafluoroethylene fiber.

[0041] The relative density of the mud for underground impact wall protection in Example 3 was measured to be 1.08, the viscosity was 18s, the sand content was 5%, the colloid rate was 95%, the water loss rate was 28ml / min, the mud skin thickness was 1.1mm / 30min, the static shear force was 2.0Pa, and the pH value was 8.8, which met the requirements for mud for strata with low density and high porosity in the technical regulations for underground impact wall inspection, which were mainly medium-coarse sand and gravel.

[0042] Example 4 Example 4 is based on Example 1, with the difference being that the amount of raw materials used in the underground impact wall slurry in Example 4 is different.

[0043] The wall protection slurry for underground anti-collision wall in Example 4 includes the following raw materials in parts by weight: 90 parts of bentonite, 0.7 parts of carboxymethyl cellulose, 1.6 parts of soda ash, 1000 parts of water, 25 parts of sodium silicate, 5 parts of nano-alumina, and 8 parts of modified polytetrafluoroethylene fiber.

[0044] The relative density of the mud for underground impact wall in Example 4 was measured to be 1.10, the viscosity was 21s, the sand content was 2%, the colloid rate was 97%, the water loss rate was 23ml / min, the mud skin thickness was 1.1mm / 30min, the static shear force was 1.8Pa, and the pH value was 9, which met the requirements for mud for strata with low density and high porosity in the technical regulations for underground impact wall inspection, where the geological conditions are mainly medium-coarse sand and gravel, and the density is low.

[0045] Example 5 Example 5 is based on Example 1, with the difference being that the amount of raw materials used in the underground impact wall slurry in Example 5 is different.

[0046] The wall protection mud for underground anti-collision wall in Example 5 includes the following raw materials in parts by weight: 90 parts of bentonite, 1.2 parts of carboxymethyl cellulose, 2.5 parts of soda ash, 1000 parts of water, 12 parts of sodium silicate, 10 parts of nano-alumina, and 16 parts of modified polytetrafluoroethylene fiber.

[0047] The relative density of the mud for underground impact wall in Example 5 was measured to be 1.10, the viscosity was 25s, the sand content was 3%, the colloid rate was 96%, the water loss rate was 20ml / min, the mud skin thickness was 1.1mm / 30min, the static shear force was 1.7Pa, and the pH value was 8.4, which met the requirements for mud for strata with low density and high porosity in the technical regulations for underground impact wall inspection, which were mainly medium-coarse sand and gravel.

[0048] Example 6 Example 6 is based on Example 1, with the difference that the average length of the modified polytetrafluoroethylene fiber in Example 6 is about 5 mm.

[0049] The relative density of the mud for underground impact wall in Example 6 was measured to be 1.12, the viscosity was 22s, the sand content was 5%, the colloid rate was 96%, the water loss rate was 15ml / min, the mud skin thickness was 1.3mm / 30min, the static shear force was 2.6Pa, and the pH value was 8.8. The mud skin thickness did not meet the requirements of the technical regulations for underground impact wall inspection for mud used in strata with mainly medium-coarse sand and gravel, low density and high porosity.

[0050] Example 7 Example 7 is based on Example 1, with the difference that the average length of the modified polytetrafluoroethylene fiber in Example 7 is about 25 mm.

[0051] The relative density of the mud for underground impact wall protection in Example 7 was measured to be 1.18, the viscosity was 24s, the sand content was 5%, the colloid rate was 95%, the water loss rate was 28ml / min, the mud skin thickness was 1.5mm / 30min, the static shear force was 2.0Pa, and the pH value was 8.8. The relative density and mud skin thickness of the mud did not meet the requirements of the technical regulations for underground impact wall inspection for mud used in strata with mainly medium-coarse sand and gravel, low density and high porosity.

[0052] Comparative Example 1 Comparative Example 1 is based on Example 1, except that the modified polytetrafluoroethylene fibers in the underground impact wall slurry in Comparative Example 1 are replaced with an equal amount of polytetrafluoroethylene fibers of similar length, i.e., the polytetrafluoroethylene fibers are not surface modified.

[0053] The preparation method of the underground anti-collision wall slurry in Comparative Example 1 comprises the following steps: S1, dissolving 0.8 parts by weight of carboxymethyl cellulose in 1 part by weight of water to prepare a 10wt% carboxymethyl cellulose solution, and letting it stand for 6 hours to obtain a carboxymethyl cellulose solution for later use; S2. Add 75 parts by weight of bentonite, 15 parts by weight of sodium silicate, 7 parts by weight of nano-alumina and the balance of water into a mixing drum, stir for 5 minutes, add soda ash, stir for 10 minutes, add 11 parts by weight of polytetrafluoroethylene fiber, stir for 20 minutes, and let stand for about 4 hours until the bentonite particles are completely hydrated and expanded to obtain a retaining mud for an underground anti-collision wall.

[0054] The relative density of the mud for underground impact wall in Comparative Example 1 was measured to be 1.21, the viscosity was 24s, the sand content was 5%, the colloid rate was 95%, the water loss rate was 43ml / min, the mud skin thickness was 1.8mm / 30min, the static shear force was 2.0Pa, and the pH value was 8.8. The relative density of the mud was too large, the water loss was too large, and the mud skin thickness was too large, which did not meet the requirements of the technical regulations for underground impact wall inspection for mud used in strata with a geological condition dominated by medium-coarse sand and gravel, low density, and high porosity.

[0055] Comparative Example 2 Comparative Example 2 is based on Example 1, except that in Comparative Example 2, the nano-alumina is replaced by an equal amount of aluminum chloride powder with the same particle size in the wall retaining slurry for the underground impact wall.

[0056] The preparation method of the underground anti-collision wall slurry in Comparative Example 2 comprises the following steps: S1, dissolving 0.8 parts by weight of carboxymethyl cellulose in 1 part by weight of water to prepare a 10wt% carboxymethyl cellulose solution, and letting it stand for 6 hours to obtain a carboxymethyl cellulose solution for later use; S2. Add 75 parts by weight of bentonite, 15 parts by weight of sodium silicate, 7 parts by weight of aluminum chloride and the balance of water into a mixing drum, stir for 5 minutes, add soda ash, stir for 10 minutes, add 11 parts by weight of polytetrafluoroethylene fiber, stir for 20 minutes, and let stand for about 4 hours until the bentonite particles are completely hydrated and expanded to obtain a retaining mud for an underground impact wall.

[0057] The relative density of the mud for underground impact wall in Comparative Example 2 was measured to be 1.15, the viscosity was 28s, the sand content was 5%, the colloid rate was 97%, the water loss rate was 48ml / min, the mud skin thickness was 1.6mm / 30min, the static shear force was 2.0Pa, and the pH value was 8.8. The viscosity of the mud was too high, the water loss was too large, and the mud skin thickness was too large, which did not meet the requirements of the technical regulations for underground impact wall inspection for mud used in strata with a geological condition dominated by medium-coarse sand and gravel, low density and high porosity.

[0058] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A wall protection slurry for underground anti-collision wall, characterized in that: The invention comprises the following raw materials in parts by weight: 75-100 parts of bentonite, 0.7-1.2 parts of carboxymethyl cellulose, 1.6-2.5 parts of soda ash, 1000 parts of water, 12-25 parts of sodium silicate, 5-10 parts of nano-alumina, 8-16 parts of modified polytetrafluoroethylene fiber; The modified polytetrafluoroethylene fiber is prepared by reacting polytetrafluoroethylene fiber with MPTMS and butyl acrylate.

2. The wall protection slurry for underground anti-collision wall according to claim 1, characterized in that: The preparation method of the modified polytetrafluoroethylene fiber comprises the following steps: adding polytetrafluoroethylene fiber, MPTMS and butyl acrylate into an organic solvent, ultrasonically stirring, adding an initiator, heating to 70-90° C., keeping the temperature constant and reacting for 1.5-3 hours; reacting again for 10-15 hours under ethanol reflux, filtering and collecting the filter residue, and drying to obtain the modified polytetrafluoroethylene fiber.

3. The wall protection slurry for underground anti-collision wall according to claim 1, characterized in that: The length of the modified polytetrafluoroethylene fiber is 5-25 mm.

4. The wall protection slurry for underground anti-collision wall according to claim 1, characterized in that: The bentonite is sodium-based bentonite with a particle size of 150-300 meshes.

5. The wall protection slurry for underground anti-collision wall according to claim 1, characterized in that: The content of montmorillonite in the bentonite is 60-80wt%.

6. A method for preparing the wall protection slurry for underground anti-collision wall according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, dissolving carboxymethyl cellulose in water to prepare a 10wt% carboxymethyl cellulose solution, letting it stand for 4-8h to obtain a carboxymethyl cellulose solution for later use; S2. Add bentonite, sodium silicate, nano-alumina and the remainder of water into a mixing drum, stir for 3-10 minutes, add soda ash, stir for 3-10 minutes, add modified polytetrafluoroethylene fiber, stir for 10-20 minutes, and let stand until the bentonite particles are completely hydrated and expanded to obtain the wall protection mud for underground anti-collision walls.

7. Application of the underground impact wall retaining slurry according to any one of claims 1 to 5 in the field of underground impact wall construction.

8. The use of the underground anti-collision wall slurry according to claim 7 in the field of underground anti-collision wall construction, characterized in that: The underground anti-collision wall retaining mud uses the waste mud after one cycle in the construction process, regenerates it, and reuses it. The regeneration method includes the following steps: T1. Pump the waste mud into a waste mud pool and let it stand for 20-30 hours to precipitate large-sized solid soil particles and fibers in the waste mud; then use the filter screen of the waste mud pool to separate the solid soil particles, fibers and mud, and collect the separated mud to obtain primary mud; T2. Add a first flocculant to the primary mud obtained in step T1, the first flocculant reacts with impurities in the primary mud to form floccules, and let it stand for 5-10 hours; add a second flocculant, the second flocculant promotes the floccules to form precipitation, and let it stand for 10-15 hours to precipitate soil particles with a particle size of less than 0.1 mm to obtain a premixed liquid; mix the premixed liquid with the raw materials used for preparing the wall protection mud for underground anti-collision walls to obtain mud, thereby completing the regeneration of the waste mud.

9. The use of the underground anti-collision wall retaining slurry according to claim 8 in the field of underground anti-collision wall construction, characterized in that: In step T2, the first flocculant is selected from one of ferric chloride, aluminum chloride and alum, and the dosage of the first flocculant is 7-12 g / L; the second flocculant is selected from one of polyacrylamide, sodium polyacrylate and starch, and the dosage of the second flocculant is 3-5 g / L.

10. The use of the underground anti-collision wall retaining slurry according to claim 8 in the field of underground anti-collision wall construction, characterized in that: In step T2, the slurry prepared using the premixed liquid includes the following raw materials in parts by weight: 25-40 parts of bentonite, 0.4-0.8 parts of carboxymethyl cellulose, 0.5-1 parts of soda ash, 800 parts of premix, 200 parts of water, 5-9 parts of sodium silicate, 3-7 parts of nano-alumina, and 8-16 parts of modified polytetrafluoroethylene fiber.